2019
DOI: 10.1590/1414-462x201900020242
|View full text |Cite
|
Sign up to set email alerts
|

Validade de medidas autorrelatadas de peso corporal e estatura em participantes do estudo São Paulo Megacity

Abstract: Resumo Introdução A utilização de indicadores válidos na avaliação do estado nutricional populacional é muito importante. Objetivo Avaliou-se a concordância entre medidas aferidas e autorrelatadas de peso corporal, estatura e IMC, e identificou-se fatores que exercem influência sobre o autorrelato. Método Estudo transversal de base populacional de adultos da Região Metropolitana de SP (N=766). Cálculo dos coeficientes de correlação intraclasse e análises gráficas de Bland & Altman foram conduzidos, aval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…19 The findings of this study did not identify differences between the measured data by sex of the participants, unlike what was described by Wilson et al, 20 whose research showed, in general, that females underestimated their weight, and that both sexes overestimated their heights, a result also pointed out in other studies, in which they self-reported their measurements with the presence of the research team. 9,10 The hypothesis of the authors of this report that there is no difference between sexes, may be related to the age group of the sample, composed of young adults, in addition to the fact that data was self-reported online and without the presence of the research team. The absence of an interviewer decreases the likelihood of concerns about social acceptance, in which information reported by participants may be biased by the desire to appear more acceptable to the research team.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…19 The findings of this study did not identify differences between the measured data by sex of the participants, unlike what was described by Wilson et al, 20 whose research showed, in general, that females underestimated their weight, and that both sexes overestimated their heights, a result also pointed out in other studies, in which they self-reported their measurements with the presence of the research team. 9,10 The hypothesis of the authors of this report that there is no difference between sexes, may be related to the age group of the sample, composed of young adults, in addition to the fact that data was self-reported online and without the presence of the research team. The absence of an interviewer decreases the likelihood of concerns about social acceptance, in which information reported by participants may be biased by the desire to appear more acceptable to the research team.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, some studies have evaluated anthropometric measurements, comparing them with self-reported data using a face-toface self-administered questionnaire, and thus, have demonstrated high agreement between both methods. [8][9][10] However, there is no consensus on the validity of Web-based self-reported information, a situation in which there are not any team members to collect the data. 5 This study seeks to fill this gap by contributing to the literature on data collection methods, i.e., to verify the validity of the Web-based selfreported measurements according to their comparison to those measured during a faceto-face assessment, which may help in further studies, as well as in the monitoring of these measurements by the Brazilian National Health System (Sistema Único de Saúde -SUS).…”
Section: Introductionmentioning
confidence: 99%